How Governance and Disasters Shape Renewable Energy Transitions: The Case of Japanese Mega‐Solar*. (6th February 2019) - Fraser, Timothy
Abstract : Objectives: This mixed‐methods study examines whether governance and disasters affect towns that host more renewable power plants, focusing on solar facilities in Japan after the 3/11 disaster. Methods: I tested the effects of various factors on multiple sizes of feed‐in tariff certified solar power plants with negative binomial models. I confirmed those effects through process tracing using 14 interviews with local stakeholders from two prefectural case studies. Results: Most prefectures boost solar power plant siting, especially for small plants 10–499 kilowatts (kW) in size. However, towns more damaged by disaster host less 10–499 kW plants because disasters create land‐use problems for solar. Conclusion: When prefectures share information about renewable resources with local residents, they can compete more evenly with extraprefectural companies. However, disaster areas face extra governance challenges when introducing solar. Good subnational governance is vital to creating a more equitable, locally engaged renewable energy transition.